2015
DOI: 10.1002/chem.201502229
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrous Amorphous Calcium Oxalate Nanoparticles from Ionic Liquids: Stable Crystallization Intermediates in the Formation of Whewellite

Abstract: The mechanisms by which amorphous intermediates transform into crystalline materials are not well understood. To test the viability and the limits of the classical crystallization, new model systems for crystallization are needed. With a view to elucidating the formation of an amorphous precursor and its subsequent crystallization, the crystallization of calcium oxalate, a biomineral widely occurring in plants, is investigated. Amorphous calcium oxalate (ACO) precipitated from an aqueous solution is described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 108 publications
(193 reference statements)
0
34
0
Order By: Relevance
“…It represents more than 80% of the dry weight of some plants and is the main component of pathological biominerals such as kidney stones. Some researchers (Qiu et al, 2004;Hajir et al, 2014;Gehl et al, 2015;Kolbach-Mandel et al, 2015) identified that the amorphous phase existed before the nucleation of calcium oxalate. However, the nature of this pre-nucleation amorphous phase remains unclear.…”
Section: Organic Biomineralsmentioning
confidence: 99%
“…It represents more than 80% of the dry weight of some plants and is the main component of pathological biominerals such as kidney stones. Some researchers (Qiu et al, 2004;Hajir et al, 2014;Gehl et al, 2015;Kolbach-Mandel et al, 2015) identified that the amorphous phase existed before the nucleation of calcium oxalate. However, the nature of this pre-nucleation amorphous phase remains unclear.…”
Section: Organic Biomineralsmentioning
confidence: 99%
“…H2O (whewellite, COM) and dihydrate CaC2O4 . 2H2O (weddellite, COD) species, although amorphous calcium oxalate can also be observed (Gehl et al, 2015;Ruiz-Agudo et al, 2017). The trihydrate form, CaC2O4 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] 4,6,[15][16][17][18][19][20] As in the case of calcium carbonate, an amorphous phase has also been detected for calcium oxalate, with a degree of hydration close to 1 molecule of water per formula unit. 21,22 On the other hand, understanding the structure and polymorphism of anhydrous calcium oxalate (COA) directly from experiment is a challenge due to the fact that it is highly hygroscopic and therefore little work has been done so far on these phases.…”
Section: Introductionmentioning
confidence: 99%